2020
DOI: 10.1101/2020.03.12.989574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioural choice emerges from nonlinear all-to-all interactions between drives

Abstract: Under the right conditions any drive can overcome nearly any other, yet studies of 1 behavioural selection predominantly focus on only one, or occasionally two behaviours. 2We present an experimental and computational framework that captures and explains the 3 resolution of conflicts between several competing motivations. We characterize neurons 4 that integrate information from all rival drives to generate an aggregate signal that urges 5 male Drosophila to transition out of mating. Experimental investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…A strong candidate for receiving the signal through the D2R is a set of eight GABAergic Copulation Decision Neurons (CDNs, labeled by NP2719-Gal4), that reside in the abdominal ganglion, in close proximity to dopaminergic neurons (Figure 2B) 17 . As expected from neurons that mediate the decision to end matings 17,20 , electrical silencing of the CDNs suppressed the increased termination caused by electrical silencing of dopamine neurons (Supplementary Figure 4C). We found that rescuing D2R expression only in the CDNs of D2R mutant animals restored normal threat resiliency (Figure 2C, Supplementary Figure 4D), without causing an increase in baseline (i.e., first mating) persistence (Supplementary Figure 4E).…”
Section: Dopamine Provides a Motivating Signal To The Copulation Deci...supporting
confidence: 59%
See 4 more Smart Citations
“…A strong candidate for receiving the signal through the D2R is a set of eight GABAergic Copulation Decision Neurons (CDNs, labeled by NP2719-Gal4), that reside in the abdominal ganglion, in close proximity to dopaminergic neurons (Figure 2B) 17 . As expected from neurons that mediate the decision to end matings 17,20 , electrical silencing of the CDNs suppressed the increased termination caused by electrical silencing of dopamine neurons (Supplementary Figure 4C). We found that rescuing D2R expression only in the CDNs of D2R mutant animals restored normal threat resiliency (Figure 2C, Supplementary Figure 4D), without causing an increase in baseline (i.e., first mating) persistence (Supplementary Figure 4E).…”
Section: Dopamine Provides a Motivating Signal To The Copulation Deci...supporting
confidence: 59%
“…For the first five minutes of a ∼23-minute mating, male flies demonstrate an apparently insurmountable motivation to persist in the face of even lethal challenges 17,33 . As the mating progresses their resiliency declines, such that by 15 minutes even relatively modest environmental changes can truncate most matings 17,20 . If supplied with an abundance of females and left to mate ad libitum , males will mate multiple times, depleting their reserves of reproductive fluid after 3-5 matings and rendering future matings unproductive 6,34 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations